Oral contraceptives, hormone replacement therapy, thrombophilias and risk of venous thromboembolism: a systematic review - Wu, Olivia; Robertson, Lindsay; Langhorne, Peter; Twaddle, Sara; Lowe, Gordon D. O.; Clark, Peter; Greaves, Mike; Walker, Isobel D.; Brenkel, Ivan; Regan, Lesley; Greer, Ian A. (Thrombosis and Haemostasis, 2005)
Combined oral contraceptives, oral hormone replacement therapy and thrombophilias are recognised risk factors for venous thromboembolism in women. The objective of this study was to assess the risk of thromboembolism among women with thrombophilia who are taking oral contraceptives or hormone replacement therapy, conducting a systematic review and metaanalysis. Of 201 studies identified, only nine met the inclusion criteria. Seven studies included pre-menopausal women on oral contraceptives and two studies included peri-menopausal women on hormone replacement therapy. For oral contraceptive use, significant associations of the risk of venous thromboembolism were found in women with factor V Leiden (OR 15.62; 95%CI 8.66 to 28.15); deficiencies of antithrombin (OR 12.60; 95%CI 1.37 to 115.79), protein C (OR 6.33; 95%CI 1.68 to 23.87), or protein S (OR 4.88; 95%CI 1.39 to 17.10), elevated levels of factor VIIIc (OR 8.80; 95%CI 4.13 to 18.75); and factor V Leiden and prothrombin G20210A (OR 7.85; 95%CI 1.65 to 37.41). For hormone replacement therapy, a significant association was found in women with factor V Leiden (OR 13.16; 95%CI 4.28 to 40.47).Although limited by the small number of studies, the findings of this study support the presence of interaction between thrombophilia and venous thromboembolism among women taking oral contraceptives. However, further studies are required to establish with greater confidence the associations of these, and other, thrombophilias with venous thromboembolism among hormone users.
Keywords: Venous thromboembolism; oral contraceptives; hormone replacement therapy; thrombophilia